Strategies for Reading Online Academic Texts: A Comparative Qualitative Study Of High- and Low-English Reading Proficiency Learners - Febiyani Febiyani; Weningtyas Parama Iswari; Maria Teodora Ping; Susilo Susilo; Noor Rachmawaty; Syamdianita Syamdianita (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Background: This study explored how students with high and low English reading proficiency employed online reading strategies when engaging with academic texts. It focused on sixth-semester of undergraduate students in Kalimantan Island. Guided by metacognitive theory, which highlights learners’ ability to monitor and regulate reading processes, this study addressed the growing importance of online academic reading in higher education. Methodology: A comparative qualitative design was employed. Six students were purposively selected based on their TOEFL reading scores to represent different proficiency levels. Data were gathered through semi-structured interviews and analyzed thematically to identify strategy use, reasons behind their choices, and the difficulties encountered. Findings: Students applied global, problem-solving, and support strategies differently based on proficiency. High-proficiency students read with clear goals, adjusted pace, and used contextual clues. Low-proficiency students focused on task completion, avoided long texts, and depended on external tools. While both slowed down when necessary, high-proficiency students showed more control. In support strategies, high-proficiency students used selective notes and minimal translation, while low-proficiency students relied on full translation. Conclusion: Strategy use was shaped by reading habits, learning experience, and proficiency level. Common difficulties included eye strain and lengthy texts, while vocabulary and technical problems varied. These findings highlight the need for proficiency-sensitive strategy instruction that also supports effective use of digital reading tools and helps students manage screen-based reading challenges. Originality: This study fills a gap by comparing online reading strategies across proficiency levels in academic contexts. It provides insight into how cognitive and contextual factors shape digital reading behavior